Improving the Quality of Early Childhood Education through Flipped Classroom Approach and SWOT Evaluation - Ida Rindaningsih; Eni Fariyatul Fahyuni; Najih Anwar; Sofiatuz Zuhro (Universitas Nurul Jadid, 2025)
The community service program at KB-TK Aisyiyah Wonoayu aims to improve the quality of early childhood education by integrating the flipped classroom model and SWOT analysis for institutional development. The implementation method includes problem identification, socialization, training of principals and teachers, application of technology, mentoring, and evaluation. It begins with a SWOT analysis to identify the strengths, weaknesses, opportunities, and threats of the school, which guides the design and implementation of the flipped classroom approach tailored to the needs of the school. Teachers are drilled to develop open modules based on flippedclassroom that allow students to learn at home through videos and engage in interactive classroom activities. The results of the study showed a 100% increase in the performance of the principal, marked by the success of the SWOT analysis and the revision of the school's vision and mission. In addition, 90% of teachers experienced an increase in the development of teaching modules and the use of AI technology and flipped classroom applications. The sustainability of this program is expected to support principals in preparing the 2025/2026 school program and maintaining the flipped classroom as an effective learning strategy, thereby increasing school competitiveness